2007
DOI: 10.3961/jpmph.2007.40.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Source of Energy Intake and Obesity in Korean Women Using the Average of Four 3-day Dietary Records

Abstract: No single macronutrient was associated with BMI when all subjects were combined. However, when stratified by age, polyunsaturated fatty acid intake in younger women, and animal protein intake in older women, were positively associated with BMI. In the future, we recommend a larger study to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…rather than total energy consumption, suggesting that calorie differences were not the only cause of obesity. 15,16 Dietary macronutrient composition have an impact on body weight independent of energy intake. The present study showed, under ad libitum condition, lowering the CHO-to-fat ratio by adding lard resulted in a rising of body weight, whereas average daily energy intake did not increase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…rather than total energy consumption, suggesting that calorie differences were not the only cause of obesity. 15,16 Dietary macronutrient composition have an impact on body weight independent of energy intake. The present study showed, under ad libitum condition, lowering the CHO-to-fat ratio by adding lard resulted in a rising of body weight, whereas average daily energy intake did not increase.…”
Section: Discussionmentioning
confidence: 99%
“…Although obesity is the result of a positive energy balance imbalance between energy intake and energy expenditure, some epidemiological studies reported that the development of obesity correlated better with dietary fat intake rather than total energy consumption, suggesting that calorie differences were not the only cause of obesity. 15,16 Dietary macronutrient composition have an impact on body weight independent of energy intake. The present study showed, under ad libitum condition, lowering the CHO-to-fat ratio by adding lard resulted in a rising of body weight, whereas average daily energy intake did not increase.…”
Section: Discussionmentioning
confidence: 99%
“…There was no difference in the TEI in all three BMI groups. However, when stratified by age, a positive correlation was observed between polyunsaturated fatty acid intake in younger women and animal protein intake in older women and BMI (Shin et al, 2007).…”
Section: Food Diaries and Dietary Assessmentmentioning
confidence: 86%